2017
DOI: 10.26486/jm.v2i2.369
|View full text |Cite
|
Sign up to set email alerts
|

Media Edutainment Segi Empat Berbasis Android: Apakah Membuat Belajar Matematika Lebih Menarik?

Abstract: Media edutainment merupakan media yang menggabungkan sisi edukasi dan hiburan secara harmonis yang dilengkapi dengan fasilitas audio, visual, dan animasi yang diharapkan dapat menumbuhkan semangat belajar siswa. Artikel ini mendiskusikan peran media edutainment dalam proses belajar siswa, dengan fokus kepada bagaimana tingkat ketertarikan dan keingintahuan dalam mempelajari materi matematika dengan menggunakan media berbasis Android. Data didapatkan menggunakan angket dan wawanara kepada 15 siswa SMP di Yogyak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 3 publications
1
2
0
3
Order By: Relevance
“…In practical terms from Table 5, although almost half of the respondents agree (41%/3,78), there is still thirty percent of respondents who disagree or agree with the games they are interested in which the games provided are interesting and easy-to-use games. This is in line with the results of the study that edutainment game media developed to help students learn mathematics to attract and arouse students' curiosity both the material learned and the game (Setyaningrum, 2016;Setyaningrum & Waryanto, 2017). These findings are under the opinion of Charsky (2010) which states that for the development of a good edutainment game it is necessary to pay attention to the characteristics of a game, the characteristics are inherently and interdependent for each melds with others and all of them have the same overall goal, which is to motivate and excite the user.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…In practical terms from Table 5, although almost half of the respondents agree (41%/3,78), there is still thirty percent of respondents who disagree or agree with the games they are interested in which the games provided are interesting and easy-to-use games. This is in line with the results of the study that edutainment game media developed to help students learn mathematics to attract and arouse students' curiosity both the material learned and the game (Setyaningrum, 2016;Setyaningrum & Waryanto, 2017). These findings are under the opinion of Charsky (2010) which states that for the development of a good edutainment game it is necessary to pay attention to the characteristics of a game, the characteristics are inherently and interdependent for each melds with others and all of them have the same overall goal, which is to motivate and excite the user.…”
Section: Resultssupporting
confidence: 84%
“…So it can be concluded that the developed game design meets the criteria of validity (4,7/5). This means that the developed game meets the necessary factors of edutainment-based media by Setyaningrum where a valid game is a game that has a good level of validity (Setyaningrum & Waryanto, 2017). Further findings are known that from the aspects of feedback, motivation, presentation design, interaction, accessibility, and standard compliance, the average score of 4.7 out of 5, which means that all the expert strongly agrees about these six aspects.…”
Section: Resultsmentioning
confidence: 60%
“…Namun dalam banyak kasus, siswa sulit dalam mengembangkan kemampuan berpikir kreatif matematika. Fitrina, Ikhsan, & Munzir (2016) (Setyaningrum, 2017).…”
Section: Pendahuluanunclassified
“…Dilihat dari perkembangan teknologi yang ada media pembelajaran yang digunaakan dapat dibedakan menjadi 4 kelompok: (1) media pembelajaran menggunakan teknologi audio visual, (2) media pembelajaran teknologi berdasarkan komputer, (3) media pembelajaran teknologi cetak, (4) pembelajaran perpaduan teknologi cetak dan digital (Setyaningrum and Waryanto 2017). Penggunaan media pembelajaran sendiri harus diselaraskan dengan yang akan disampaikan kepada peserta didik dan yang dibutuhkan oleh peserta didik.…”
Section: Pendahuluanunclassified